Pembelajaran Berbasis Pengalaman Sebagai Inti Teori Konstrukturvisme John Dewey Dalam Perspektif Psikologi Pendidikan - muminin, Nashrul; Yurniati, Yurniati; Perimasanti, Riza Dyah Ayu; Syafitri, Lely Nur Hidayah (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
This study examines experiential learning within John Dewey's constructivist theory from an educational psychology perspective. Using a literature review method, this study examines the role of direct experience in shaping student understanding and development. The results indicate that experiential learning enhances conceptual understanding, reflective attitudes, social skills, and learning motivation. Dewey's approach has proven relevant to modern education, which demands active and contextual learning. It is recommended that teachers integrate real-life experiences to create meaningful and sustainable learning.